2019
DOI: 10.1111/jvh.13106
|View full text |Cite
|
Sign up to set email alerts
|

HBV coinfection with HCV alters circulating Tfh cell distribution and impairs HCV neutralizing antibody responses

Abstract: Hepatitis C virus (HCV) and hepatitis B virus (HBV) coinfection reciprocally influences viral replication and host defence responses. This study aimed to investigate the impact of HBV coinfection on circulating T follicular helper cell (cTfh) distribution and the HCV neutralizing antibody (nAb) response. HCV neutralizing antibody re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Collectively, despite the bias of using phenotypically altered in vitro -expanded cells, we could confirm our ex vivo results on HCV-specific CD4 T cells that showed an overlapping Tfh/Th1 phenotype and gene expression profile ( 26 ) and we were able to demonstrate superior Tfh functionality of these cell population on the antigen-specific level. Our results strongly support previous findings that the B cell or the neutralizing antibody response to HCV infection are positively correlated to the Tfh1 rather than Tfh response ( 16 18 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Collectively, despite the bias of using phenotypically altered in vitro -expanded cells, we could confirm our ex vivo results on HCV-specific CD4 T cells that showed an overlapping Tfh/Th1 phenotype and gene expression profile ( 26 ) and we were able to demonstrate superior Tfh functionality of these cell population on the antigen-specific level. Our results strongly support previous findings that the B cell or the neutralizing antibody response to HCV infection are positively correlated to the Tfh1 rather than Tfh response ( 16 18 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…One of the most prominent subsets of cTfh cells are those with overlapping Th1 characteristics, often referred to as cTfh1 cells. They have been shown to correlate with antibody responses during infections with HCV and HIV (14)(15)(16)(17)(18)24) and after vaccination (20)(21)(22)(23) and are the dominant subset within circulating HCV-specific CD4 T cells after DAA therapy (26). However, studies of their actual B cell helper capacity were hampered by the scarcity of this cell population and consequently limited to the bulk level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has investigated the impact of co-existing HBV on circulating T follicular helper cell (Tfh) distribution and the HCV neutralizing antibody response [47]. Patients with HCV mono-infection (n = 83) and HBV/HCV co-infection (n = 78) were both enrolled.…”
Section: Viral Interactions: With Emphasis On Mechanisms Of Hbv Reactmentioning
confidence: 99%
“…The results of Spaan et al (14) showed that the expression of ICOS + Tfh cells and cytokine IL-21 increased significantly in the course of acute HCV infection, suggesting that cTfh cells play a key role in the regulation of immune response to acute HCV infection. Alternatively, IL-21 receptors are widely distributed in B cells and cTfh cells, which can positively promote the expression of CXCR5 in patients with acute hepatitis C through autocrine signaling (9,15,16).…”
Section: Cd4+cxcr5+ctfh Ratio and Hcv Rna Content In Infected Groupmentioning
confidence: 99%